The Effect of Sample Placement in the Furnace during the Heat Treatment Process of 7075-T6 Aluminum Alloy on Microstructure, Hardness, and Electrical Conductivity - Dhaneswara, Donanta; Rindharto, Hardi; Aqilafif, Muhammad Syauqi (UI Scholars Hub, 2022)
This paper reports the effects of sample placement during the heat treatment on the microstructural morphology and mechanical properties of 7075 Al alloy such as hardness value and electrical conductivity. The material was in the formed of Al alloy sheets where samples were machined into a square with dimensions of 1.5 x 1.5 inch. The 7075-T0 Al alloy as samples were given heat treatment by precipitation hardening (aging) at temperature 120°C for 24 hours, so it becomes 7075-T6 Al alloy. Samples were subjected to some mechanical tests and the morphology of the resulting microstructures were characterized by optical microscopy. The variable was the placement of samples in the furnace which is based on the differences of the 7075 Al alloy properties, from aging process T0 to T6, in microstructure, hardness value and electrical conductivity even though the tools, materials and treatment given are the same. The study showed that as far as the sample from the furnace door, hardness values were increased while the electrical conductivity decreased and it was proportional to the dispersion of precipitates that occurred.